Abnormal light propagation and the underdetermination of theory by evidence in astrophysics - Asenjo, F; Hojman, S; Linnemann, N; Read, JAM (Elsevier, 2023)
We investigate the propagation of certain non-plane wave solutions to Maxwell’s equations in both flat and curved spacetimes. We find that such solutions (or rather parts of them) exhibit accelerative behaviour, and in particular do not propagate on straight lines. Having established these results, we then turn to their conceptual significance—which, in brief, we take to be the following: (i) one should not assume that the part of electromagnetic waves from outer space that is subject to detection is localised onto null trajectories; therefore (ii) astrophysicists and cosmologists should at least be wary about making such assumptions in their inferences from obtained data, for to do so may lead to incorrect inferences regarding the nature of our universe.